Uso do gênero discursivo tira no ensino de texto multimodal - Reis, Natházia de Almeida Fonsêca (2018)
Addressing the challenge of the school to train competent readers and, knowing the difficulties encountered by students and teachers regarding the study of texts in the classroom, this dissertation highlights the importance of working with the genre tirinha as a support to subsidize language teaching, focusing on the development of reading skills with multimodal text, through the aforementioned genre, with the focus of developing / expanding pupils' reading competence and critical thinking, as well as stimulating the taste for reading, from of the use of comics, as a complementary strategy of text teaching. Although there is still much to be done in the teaching of mother tongue in Brazil, it is worth emphasizing the innovative actions of public policies for Elementary Education, such as curricular changes and the organization of teaching processes. Among these actions, aimed at improving the quality of reading and writing learning, the National Curriculum Parameters of Portuguese Language - PCNs (BRASIL, 1997) stand out. Actions that aim to meet the growing demand of multiletramento in Brazil and depend on a school that forms citizens capable of thinking creatively and of interacting using different languages. Thus, the objective is an educational process that allows the student access to knowledge through a critical literacy, instrumentalizing it to understand discourses of various media and cultures and involve them in the construction of the senses. Therefore, we think of a dynamic text teaching that associates verbal and non-verbal language, in which the student is able to familiarize himself with the characters and establish connections with his daily life. The comic strip is considered the smallest cell within the genres that encompasses comic books and is widely used in textbooks, web sites, distance education, among other segments, for addressing various themes, in various contexts, historical and social. The structure of the present study consists of reading, interpreting and producing comic strips in the classroom, working on its characteristics, with emphasis on textual interpretation and production.